Application of Project Based Learning with Scientific Article Analysis Method to Improve Student Learning Outcomes in Education Profession Courses - Hikmawati Hikmawati (Journal of Science and Science Education, 2022)
The Education Profession course is a course that equips students so that one day they can carry out the main tasks of professional teachers, namely educating, teaching, guiding, directing, training, assessing, and evaluating students. The purpose of this research is to improve student learning outcomes in the Professional Education course through the application of Project Based Learning (PjBL) using the scientific article analysis method. This research was conducted in 6 meetings starting from March 2 2022 to April 6 2022. The subjects of this research included 22 students who attended the Education Profession course in Class II-C, in the Physics Education Study Program, University of Mataram. The research instrument for obtaining data on student learning outcomes uses essay tests given at the beginning of the meeting and at the end of the meeting. The increase in the score of learning outcomes after treatment in the form of implementing PjBL with the scientific article analysis method is calculated by the N-gain test. The results showed that the pre-test score was 51.2, while the post-test score was 80.3. Therefore, the N-gain value is 60.4 which is in the medium category. Thus, the implementation of PjBL using the scientific article analysis method has improved student learning outcomes in the Education Professions course.